2013
DOI: 10.1155/2013/484535
|View full text |Cite
|
Sign up to set email alerts
|

NRAMP1, VDR, HLA-DRB1, and HLA-DQB1 Gene Polymorphisms in Susceptibility to Tuberculosis among the Chinese Kazakh Population: A Case-Control Study

Abstract: Background. To explore the potential role of natural-resistance-associated macrophage protein 1 (NRAMP1) gene, vitamin D receptor (VDR) gene, (human leukocyte antigen, (HLA-DRB1) HLA) -DRB1 gene, and HLA-DQB1 gene polymorphisms in susceptibility to tuberculosis (TB) in the Chinese Kazakh population. Methods. A case-control study was performed on the Chinese Kazak population. Genetic polymorphisms of NRAMP1 gene (3′UTR) and VDR gene (TaqI and FokI) were analysed using polymerase chain reaction-restriction fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 29 publications
0
42
0
Order By: Relevance
“…There were no significant differences of the Taq1-Tt and tt genotype frequencies between TB patients and healthy controls (16).…”
Section: The Frequency Of the F-t-b And F-t-b Haplotypes Of The Vdr Fmentioning
confidence: 72%
See 1 more Smart Citation
“…There were no significant differences of the Taq1-Tt and tt genotype frequencies between TB patients and healthy controls (16).…”
Section: The Frequency Of the F-t-b And F-t-b Haplotypes Of The Vdr Fmentioning
confidence: 72%
“…In addition, there is other evidence that emphasizes the variations in ethnicity for the susceptibility to TB (15). Different candidate genes have been examined in associated studies to evaluate the identity of the TB 'susceptibility factors,' including human leukocyte antigen (16,17), natural-resistance-associated macrophage protein 1 (16,17), VDR (11,16), cluster of differentiation 14 (18), interleukins (19) and Toll-like receptors (20).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a Taiwanese aboriginal casecontrol study revealed that individuals possessing one of the three polymorphism of the SLC11A1 gene have higher susceptibility to tuberculosis, with those who are heterozygous for the INT4 polymorphism being at greatest risk [6]. Similar findings have also been reported in Chinese, Korean, Japanese, Iranian, AfricanAmerican and Caucasian populations [7][8][9][10][11][12]. In bovine studies, a genomic region of the 3'UTR of the SLC11A1 cDNA gene sequence is associated with natural resistance against bTB.…”
Section: Introductionmentioning
confidence: 57%
“…110 Furthermore, HLA-DRB1*04 and HLA-DQB1*02:01 were associated with TB in Chinese patients. 111 Thus, several studies of HLA association with pulmonary tuberculosis have been carried out in Chinese, 111,112 Korean, 113 Indonesian, 114 Indian 115-121 and Russian patients. 122 Of the numerous Indian studies on HLA association with pulmonary tuberculosis, the earlier studies focussed on association of HLA Class I antigens 115,116 and later in family studies in North India 118,120 and South India 117,121 that focussed on HLA Class II antigens.…”
Section: Hla and Mycobacterium Tuberculosis Infectionmentioning
confidence: 99%